Mixed Ligand Complexation of Pr(III), La(III) and Ce(III) with Some Organic Ligands:A Potentiometric Study - SHAKOOR, M.A.; HUSSAIN, SYED (Asian Journal of Chemistry, 2010)
Interaction of La(III), Ce(III) and Pr(III) with N-2-mercapto propionyl glycine, phenyl alanine and tyrosine at 25°C in aqueous medium was studied. pH titration data based on Calvin-Bjerrum titration technique were employed for the calculation of proton-ligand and metal-ligand stability constants.